Peran Komisi Perlindungan Anak dalam Mengatasi Kasus Bullying - Syifa, Nazwa; Fitri, Annida; Luthfiana, Anik Priamita; Hafidzi , Anwar (Interdisciplinary Explorations in Research Journal, 2025)
Bulliying is an issue with significant negative impacts on children's mental and social health. The Indonesian Child Protection Commission (KPAI) plays a crucial role in handling bulliying cases through advocacy, mediation, and public education. This article aims to evaluate the effectiveness of KPAI in addressing bulliying cases and identify challenges faced by this institution. Analysis results indicate that while KPAI has shown effectiveness in certain areas, it still encounters challenges, such as limited resources and low public awareness. To enhance its role, it is recommended that KPAI strengthen partnerships with schools, increase public awareness, and utilize technology to monitor cyberbulliying. In conclusion, increased cross-institutional synergy can enhance KPAI's effectiveness in creating a safer environment for Indonesian children.